MECHANISM OF DEDUCTIONS OF THE STRUCTURAL FUND AND MEMBERSHIP FEES FROM THE FINANCIAL STATEMENTS SUBMITTED BY THE LAWYER - Turaev Shakhriyor Shodiyorovich (Scholar Express Journals, 2025)
The article shows the mechanisms for developing the infrastructure of advocacy structures, improving the principles of their operation by covering the administrative costs of the structure, withholding and paying membership fees by lawyers in efficient ways, effective use of advocacy services, how to withhold deductions from entities of the advocacy structure in convenient ways, and improving these deductions.
Keywords: financial statements; fund payment; membership fee payment